2022
DOI: 10.1038/s41598-022-12894-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of extra-anatomical bypass on coarctation fluid dynamics using patient-specific lumped parameter and Lattice Boltzmann modeling

Abstract: Accurate hemodynamic analysis is not only crucial for successful diagnosis of coarctation of the aorta (COA), but intervention decisions also rely on the hemodynamics assessment in both pre and post intervention states to minimize patient risks. Despite ongoing advances in surgical techniques for COA treatments, the impacts of extra-anatomic bypass grafting, a surgical technique to treat COA, on the aorta are not always benign. Our objective was to investigate the impact of bypass grafting on aortic hemodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 116 publications
(167 reference statements)
0
5
0
Order By: Relevance
“…In contrast, in the present study, we found that elevated pressure (≥100 Pa) correlated independently with aneurysm growth. As discussed by Sadeghi et al [ 6 ], although the WSS has been recognized to influence the progression of vascular diseases, including AAoA progression and rupture, it is not yet well established in clinical practice as a tool for understanding prognosis or planning interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in the present study, we found that elevated pressure (≥100 Pa) correlated independently with aneurysm growth. As discussed by Sadeghi et al [ 6 ], although the WSS has been recognized to influence the progression of vascular diseases, including AAoA progression and rupture, it is not yet well established in clinical practice as a tool for understanding prognosis or planning interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Surgery is planned based on the diameter of the ascending aorta, obtained by imaging, under periodic monitoring [ 1 , 2 , 3 ]. In this context, in recent years, specific geometry studies have emerged to assess the risk of various cardiovascular diseases [ 4 , 5 , 6 ]. However, comparisons of aortic diameter are hampered by the asymmetry of this artery [ 7 ], and it has been shown to be an insufficient risk predictor in patients with AAoA [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we considered only the experimental component as a validation and comparison of pressure methods. Furthermore, several studies proposed the integration of computational fluid dynamics (CFD) with 4D-flow MRI to overcome the spatial and temporal limitations of 4D-flow MRI [40,65,66]. In particular, finite element methods can be used to discretize the in vivo 4D-flow velocity field and estimate the pressure maps more accurately [10,67].…”
Section: Discussionmentioning
confidence: 99%
“…The previously created model, C3V-LPM, was validated against clinical catheterization data in forty-nine AS patients with a substantial inter- and intra-patient variability with a wide range of disease 41 . In addition, some of the sub-models of the patient-specific LPM algorithm have been used and validated previously 30 , 31 , 42 – 52 , with validation against in vivo cardiac catheterization 53 , 54 in patients with vascular diseases, in vivo MRI data 55 in patients with AS, and in vivo MRI data 56 – 58 in patients with coarctation and mixed valvular diseases.…”
Section: Methodsmentioning
confidence: 99%